IDENTIFIKASI MISKONSEPSI SISWA MENGGUNAKAN CERTAINTY OF RESPONSE INDEX PADA OPERASI HITUNG BILANGAN - Dhimas Ardya R.S.; Harina Fitriyani (Universitas Muhammadiyah Semarang, 2017)
Student is always make basic concept error on some matter in math lesson. Common concept error is called misconception. To identify misconception on students, then used Certainty of Response Index (CRI) technique were developed by Saleem Hasan. In CRI, students are asked to provide a degree of certainty in answering a problem with concept, law, or principles that already understood. This research aim to know whether or not there is misconception and causes of misconception arise in solving the integer count and fractional operation problem based on CRI techniques. This research is a descriptive qualitative research. The subject of this research is students grade VII-F SMPN 1 Wonosari who has misconception. The object research is the student misconception on solving the integer count and fractional operation problem based on CRI technique. The data collecting technique is problem solving test and interview. The data analysis used Miles and Huberman moel, which is data reduction, data presentation, and making conclusion. The results of this research showing that there is misconception from the subject research on solving the integer count and fractional operation problem. The causes of misconception from the subject were the pressure of the practical aspect, the error of the word meaning, and simplification. Keywords: Certainty of Response Index (CRI), misconception, integer count andfractional operation.